Comportamiento de la Frecuencia Cardiaca en Test progresivos; algunas variables a considerar (Revista Educación Física Chile, 2022)
Heart Rate (HR) has been used as a physiological variable for the evaluation and prescription of exercises for different populations. Due to its simplicity, many tests of cardio respiratory capacity base their interpretations on the HR behavior. The purpose of this review is to extend the prism of the originating information of the progressive HR curve in tests, considering some variables such as: the point of flexion and deflection of the HR, the Autonomic Nervous System modulation and its effect on HR variability on the progressive exercise. Thus, this study intend to discuss about the use of the HR to predict some physiological events, such as the behavior of the blood lactate during training.
Keywords: Heart Rate, progressives test, autonomic Nervous System